Surasundari on the eastern wall of the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
The surasundari (celestial damsel), presently faceless, stands gracefully with her voluptuous body adorned with exquisite ornaments, on the eastern wall of the garbhagriha (sanctum sanctorum. Although her right hand is raised and damaged, she holds a fine scarf in her left hand near her belly, wrapping it around her arms. Her lower body is veiled by a fine translucent garment. A small creature is depicted moving upward on her left leg. The surasundari vividly embodies sensual beauty, in stark contrast to the tranquil and composed posture of the ascetic. There is a kalasha (water pot) placed at the bottom near her feet with foliage, symbolizing abundance and growth as does the female body.